739 Ozone therapy vs. classical treatment in musculoskeletal disorders (Balneo and PRM Research Journal, 2024)
With aging and weight gain, the population is significantly overweight and faces additional pressure on vertebral and peripheral joints (ankles, knees, hips, shoulders), which affects muscles, tendons, ligaments, and nerves. Muscle contraction, translated by pain, sends the patient to the doctor. Lumbar and cervical spine disorders occur in 70-80% of the world's population during their lifetime. They are a major problem because they reduce the quality of life and increase the costs borne by health services and patients. There are multiple therapeutic options, both classic medication and alternative treatment, to combat pain for a longer or shorter period. Relief or suppression of pain, the dominant symptom in the manifestations of degenerative arthritic diseases, is an important goal of treatment, ultimately improving the quality of life. Patients, for various reasons, frequently seek alternative therapies, especially to surgical treatment. Finding the most comprehensive treatment is often a challenge. If we consider the benefit that a treatment (therapy) should bring to the health condition, then an individualized therapeutic plan must be chosen. A retrospective study on the effects of ozone and platelet-rich plasma (PRP) treatment compared to classic medication shows the role of ozone therapy in pain relief and the beneficial effect of this therapy, especially in combination with PRP, over a longer period.